Act Tough and Soft: Video Monitoring, Hongbao Gifts, and the Job Satisfaction of Domestic Workers - Yang, Anuo; Fu, Shuangle; Liu, Linping; Fan, Changyu; Jilili, Maitixirepu (Frontiers in Public Health, 2022)
There is a rapidly growing demand for domestic services among urban families in China. However, domestic work remains a low-status occupation with a high turnover rate. Focusing on the job satisfaction of domestic workers is useful to interpret this phenomenon. We investigate how the job satisfaction of domestic workers in China is affected by to two distinct labor control strategies used by their employers: the installation of video-monitoring devices in employers' homes (a “tough” control strategy), and the Chinese custom of giving monetary gifts, or “hongbao” (a “soft” control strategy). By analyzing data from surveys of domestic workers in four cities in China (N = 699), we find that video monitoring in employers' homes negatively impacts domestic workers' job satisfaction, and that hongbao gifts from employers significantly promote domestic workers' job satisfaction. The analysis of the causal mechanism based on a structural equation model suggests that video monitoring can increase the discrimination that domestic workers perceive, which in turn reduces their job satisfaction. In particular, we find that domestic workers' perception of discrimination completely mediates the effect of video monitoring on their job satisfaction. However, we also find that hongbao gifts significantly reduce domestic workers' perceptions of discrimination, and thus promote their job satisfaction; that is, the relationship between hongbao gifts and job satisfaction is partially mediated by discrimination. Our study provides a more comprehensive understanding of Chinese employers' labor control strategies and their effects on the job satisfaction of domestic workers.